Keeping Secrets, Telling Lies: Fictions of the Artist and Author in the Novels of Margaret Atwood - McWilliams, Ellen (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This article explores how Margaret Atwood's novels, in particular Cat's Eye and The Blind Assasin, engage with the generic paradigms of the Bildungsroman and Künstlerroman, and, in doing so, respond to what Atwood describes as "the paradoxes and dilemmas" traditionally encountered by the female artist and author.